2023
DOI: 10.1108/el-06-2023-0163
|View full text |Cite
|
Sign up to set email alerts
|

Information systems success in libraries: a meta-analysis of ISSM and future direction

Irfan Ali,
Nosheen Fatima Warraich

Abstract: Purpose The purpose of this study is to investigate the relationships between the information system success model constructs including information quality (IQ), system quality (SysQ) and service quality (ServQ) with user satisfaction (US) and intention to use (IU). Design/methodology/approach A meta-analysis approach was used to achieve the objectives. For this purpose, the PRISMA-P guideline was used, and a search strategy was designed to search in three indexing databases including Google Scholar, Scopus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The findings revealed that system factors and content factors have a significant impact on students' satisfaction with YouTube, which further influences their intention to use the platform for learning purposes. Ali and Warraich (2024) examined information systems success in libraries. The results show that information quality, system quality and service quality positively influence satisfaction with library systems.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…The findings revealed that system factors and content factors have a significant impact on students' satisfaction with YouTube, which further influences their intention to use the platform for learning purposes. Ali and Warraich (2024) examined information systems success in libraries. The results show that information quality, system quality and service quality positively influence satisfaction with library systems.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%